2015
DOI: 10.1080/07315724.2015.1080111
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Omega-3 Fatty Acids in Diets

Abstract: The article is a summary of Dra. Carmen Gómez Candela's presentation at the Science in Nutrition 3rd International Congress in Milan, March 2014. The article covers omega-3 fatty acids use in different medical areas and several institutions' opinions in relation to the topic. Omega-3 acids are essential fatty acids. A certain amount of omega-3 is needed in our daily diet; however, the usual consumption is generally less than the recommended amount. Changes in dietary patterns in the course of history have led … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…However, there is a disproportionally high proportion of n-6 FAs and low proportion of n-3 FAs in our current dietary structure. This results in a high ratio of n-6/n-3, which is associated with cardiovascular disease, inflammation and cancer (1)(2)(3). The n-3 FAs are long-chain polyunsaturated FAs.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a disproportionally high proportion of n-6 FAs and low proportion of n-3 FAs in our current dietary structure. This results in a high ratio of n-6/n-3, which is associated with cardiovascular disease, inflammation and cancer (1)(2)(3). The n-3 FAs are long-chain polyunsaturated FAs.…”
Section: Introductionmentioning
confidence: 99%
“…In further metabolic transformations, PUFA n-6 compete at the enzymatic level with PUFA n-3, therefore the high dietary intake of PUFA n-6 inhibits the synthesis of EPA and DHA while enhances the synthesis of arachidonic acid. This in turn may prevent the body from maintaining homeostasis, therefore the proper ratio of PUFA n-6/n-3 should be kept (Harper and Jacobson, 2001;Benatti et al, 2004;Gomez-Candela et al, 2015). Another study found also that in addition to its strong lipid-lowering effect, strawberry seed oil may adversely affect the metabolism of microorganisms in the distal part of the intestine (Jurgoński et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Fish, such as mackerel, salmon, sardines, halibut, herring, and tuna, in the human diet is the major source of n-3 PUFAs, containing docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA). Quite a few kinds of vegetables and vegetable oil, such as flaxseeds, canola, pumpkin seeds, flaxseed oil, canola oil, and perilla seed oil, also can provide n-3 PUFAs, such as alpha-linolenic acid (ALA), which can be converted to EPA and further to DHA by a desaturase enzyme [ 6 ]. Isotope-labeled ALA trials suggested that the conversion of natural ALA to EPA is between 0.2% and 21% and further to DHA is between 0% and 9% [ 7 ].…”
Section: Subsets Sources and Metabolism Of N-3 Pufasmentioning
confidence: 99%